长链非编码RNA MALAT-1基因的敲除抑制人喉鳞状细胞癌Hep-2细胞的增殖和迁移 (Nan Fang Yi Ke Da Xue Xue Bao, 2018)
OBJECTIVE: To investigate the effect of knocking down long chain non-coding RNA MALAT-1 gene on the biological behaviors of human laryngeal squamous cell carcinoma Hep-2 cells. METHOD: With immortalized nasopharyngeal epithelial (NPE) cell line NP-69 as the reference, MALAT1 expression in FaDu, Hep-2 and nasopharyngeal carcinoma CNE-2Z cells were detected using real-time PCR. Hep-2 cells were transfected with shmalat1 lentivirus and the expression of MALAT1 was detected. MTT assay, flow cytometry, Transwell assay and M Atrigel invasiveness test were used to evaluate the effect of MALAT-1 knockdown on the proliferation, cell cycle, cell apoptosis, migration, and invasiveness of Hep-2 cells. RESULTS: Compared with NP-69 cells, Hep-2 cells, FaDu cells, and CNE-2Z cells all showed significantly increased MALAT-1 expression. In Hep-2 cells, knockdown of MALAT-1 significantly inhibited the cell proliferation, increased the cell percentage in S phase (P < 0.01), decreased the cell percentage in G2/M phase (P < 0.01), and attenuated the migration and invasiveness of the cells. CONCLUSION: MALAT-1 is over-expressed in laryngeal squamous cell carcinoma, and knocking down MALAT-1 gene can significantly suppress the proliferation, invasion and migration and promotes apoptosis of the cancer cells.